2012
DOI: 10.1111/j.1474-9726.2012.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotyping of aging in single yeast cells using a novel microfluidic device

Abstract: SummaryBudding yeast has served as an important model organism for aging research, and previous genetic studies have led to the discovery of conserved genes/pathways that regulate lifespan across species. However, the molecular causes of aging and death remain elusive, because it is very difficult to directly observe the cellular and molecular events accompanying aging in single yeast cells by the traditional approach based on micromanipulation. We have developed a microfluidic system to track individual mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 39 publications
6
132
0
Order By: Relevance
“…Recently, such devices have been designed that enable the tracking of yeast cells throughout their lifespan, making it possible to record and study cellular phenotypic changes during aging (21)(22)(23). However, many issues prevent the use of microfluidic devices in a high-throughput manner for lifespan screens.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, such devices have been designed that enable the tracking of yeast cells throughout their lifespan, making it possible to record and study cellular phenotypic changes during aging (21)(22)(23). However, many issues prevent the use of microfluidic devices in a high-throughput manner for lifespan screens.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Fourth, the micropad design often allows more than one cell to be trapped; multiple cells can be trapped underneath one micropad, whereas no cells are trapped under others. Finally, in one of the designs, cell-surface labeling and chemical modification of the device are required, which has proven to be technically challenging for fabrication and to introduce adverse effects on replicative lifespan (23).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation
“…To connect the asymmetric division in young cells to the aging phenotype in old cells, we tracked how these proteins change over time in single mother cells throughout their lifespan, using a recently developed microfluidic device (32,33). We analyzed Did2p and Tpo3p, which represent a protein involved in endosomal sorting/endosome-to-vacuole transport and a nitrogen source transporter, respectively.…”
Section: Mother-enriched and Lifespan-limiting Proteins Tend To Accummentioning
confidence: 99%
“…[18] They attached the yeast cells on a wall coated by avidin to track individual mother cells throughout their whole lifespan, and found that the aging of cells was characterized by an increased general stress and a progressive lengthening of cell cycle for the last few cell divisions. [19] The Walkmoto group demonstrated that growth noise among single cells could cause clonal populations of Escherichia coli to divide faster than the mean doubling time of their constituent single cells. [20] Recently, with the help of a "mother machine" device, the Jacobs-Wagner group discovered that microorganisms like E. coli and C. crescentus achieved cell size homeostasis by growing the same volume or length between divisions.…”
Section: High Resolutionmentioning
confidence: 99%